Early miocene post-collisional calc-alkaline magmatism along the easternmost segment of the periadriatic fault system (Slovenia and Croatia) - Altherr, Rainer; Lugovíć, Boško; Meyer, Hans-Peter; Majer, Vladimir (Mineralogy and petrology, 1995)
Early Miocene calc-alkaline igneous rocks from the easternmost segment of the Periadriatic fault system can be subdivided into two series of different alkalinity: (1) Volcanics which occur in the vicinity of the Velenje-Rogatec Line range from high-alumina basalt via low-K and medium-K andesites to medium-K dacites. (2) In the Pohorje Mountains mafic rocks are lacking. A high-K tonalitic pluton crystallized at pressures of about 0.7 GPa as indicated by Al-in-hornblende barometry and accessory magmatic epidote. Rapid exhumation of the tonalite during dextral transtension along the Periadriatic fault system is indicated by tonalitic pebbles in Helvetian (?) clastic sediments. High-K andesitic to dacitic volcanics are interlayered with, and dikes cut, the clastic sediments.